PREPARATION OF OINTMENT AND EVALUATION OF SYNERGETIC EFFECT OF POLYHERBAL EXTRACTS FOR ANTIDIABETIC ACTIVITY - HOGGUI Ghoufran; HANI Med Laid (Université of Eloued, 2024)
The aim of the present study was to evaluate synergetic effect of antioxidant and antidiabetic potential of methanolic and aqueous extracts of Olea europaea L., Myrtus Communis L., Artemisia herba alba L., Commiphora myrrha L. The extracts was analyzed by qualitative and quantitative tests, the antioxidant activity of extracts was determined using: TLC bioautographic test, DPPH scavenging method, reducing power and total antioxidant assay as well as alpha-amylase inhibitory activity of aqueous extract was carried out. In vivo antidiabetic activity of aqueous extract was orally administered to normoglycemic and alloxan-treated diabetic rats at 100, 300 and 500 mg/Kg to determine their hypoglycemic effect using metformin as control. The phytochemical screening carried out showed the presence of tannins, sterols and triterpenes, saponins, flavonoids and terpenoids. The qualitative test revealed yellow spots on the TLC plates sprayed with DPPH, and quantitative analysis showed significant levels of flavonoids with an amount of 439.93 mg EQ/g DW and 357.41 mg EQ/g DW in methanolic and aqueous extracts respectively. It was found that extracts exhibited the maximum inhibition of DPPH with 61.47% and 45.24% for the same order of extracts tested at 0.5 mg/mL, these extracts have the power to reduce iron and phosphomolybdate ion. Alpha-amylase inhibition activity of aqueous extract attaints 60% of inhibition in comparison to acarbose (80%), respectively. Aqueous extract exerted signicant decline in the fasting blood sugar in diabetic animals, however an increase in body weight was mentioned. It was also noted that this extract caused an improvement in biochemical profiles and improved the oxidative stress status in the tissues studied. Indeed, the decrease in MDA concentrations and the increase in GSH and GPx levels in the organs of treated rats were recorded. The histological study showed the beginning of regeneration of the pancreatic cells, and there was a significant improvement in the condition of the hepatocytes with a disappearance of vascular congestion in the liver. On the other hand, the histological study of the skin of the foot which has undergone massage of the ointment does not exert a toxic or irritating effect. Therefore, this polyherbal combination has the potential to be further developed as complex phytotherapeutic remedy for the treatment of diabetes.
Keywords: Polyherbal; polyphenols contents; antioxidant activity; α-amylase; oxidative stress and in vivo antidiabetic activity.